The ethnic wage gap may hinder the attractiveness of the chiropractic profession to attract and retain talent - Gupta, Neeru (My University, 2025)
Given global population aging and increasing but widespread unmet needs for medical rehabilitation services, better understanding of the factors favouring or hindering the recruitment and retention of chiropractors is especially valuable. In particular, it has been argued that the chiropractic profession lags behind the physician profession in concerted efforts to advance diversity across the education-to-practice and leadership pipelines. This study used 2021 Canadian census data to characterize chiropractic practitioners aged 25–54 in terms of demographic representation and earnings differentials underlying the (un)attractiveness of this health profession to new talent.
Keywords: Health; Immigration and ethnocultural diversity; Labour; Population and demography